Letters from Togo - Blake, Susan Louise, 1946- (Singular lives., 1991)
Blake's adventurous essays--her Letters from Togo--are based on the letters she wrote to her friends from Lomé, the West African capital where she spent a Fulbright year teaching American literature from 1983 to 1984. As Blake begins the process of making sense out of a vibrant, seeming anarchy, we are pulled along with her into the heart of Togo--a tiny dry strip of a country no one can even find on a map. With her delightful prose and insight for detail Blake introduces us to Mahouna, her housekeeper, who runs a cold drink business from his refrigerator in a country where electricity is unre.